2018
DOI: 10.1093/nar/gky386
|View full text |Cite
|
Sign up to set email alerts
|

Base-flipping dynamics from an intrahelical to an extrahelical state exerted by thymine DNA glycosylase during DNA repair process

Abstract: Thymine DNA glycosylase (TDG) is a DNA repair enzyme that excises a variety of mismatched or damaged nucleotides (nts), e.g. dU, dT, 5fC and 5caC. TDG is shown to play essential roles in maintaining genome integrity and correctly programming epigenetic modifications through DNA demethylation. After locating the lesions, TDG employs a base-flipping strategy to recognize the damaged nucleobases, whereby the interrogated nt is extruded from the DNA helical stack and binds into the TDG active site. The dynamic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 111 publications
2
47
0
Order By: Relevance
“…Genetic variations, such as SNPs of DNA repair genes, modify DNA repair efficiency by changing protein function and therefore increase the risk for various cancers (de Boer, ; Xi et al, ), such as chronic pulmonary disease and lung malignancy (Arimilli, Schmidt, Damratoski, & Prasad, ; Kheradmand et al, ). Among DNA repair genes, the TDG gene was identified as the first mismatch‐specific enzyme playing a key role in recognizing and correcting a variety of damaged and/or mismatched nucleotides (Cortazar et al, ; Da & Yu, ). All data support the hypothesis that TDG genetic polymorphisms and tobacco smoking may lead to the development of smoking‐related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations, such as SNPs of DNA repair genes, modify DNA repair efficiency by changing protein function and therefore increase the risk for various cancers (de Boer, ; Xi et al, ), such as chronic pulmonary disease and lung malignancy (Arimilli, Schmidt, Damratoski, & Prasad, ; Kheradmand et al, ). Among DNA repair genes, the TDG gene was identified as the first mismatch‐specific enzyme playing a key role in recognizing and correcting a variety of damaged and/or mismatched nucleotides (Cortazar et al, ; Da & Yu, ). All data support the hypothesis that TDG genetic polymorphisms and tobacco smoking may lead to the development of smoking‐related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Again, we cannot rule out that a small amount of contaminating duplex contributes to the product yield for the fast phase, or, in contrast, this phase corresponds to an NCP population readily accessible to TDG. Recent molecular dynamic simulations examining the steps after binding and up to but excluding bond cleavage have indicated that the rate-limiting step for TDG on duplex substrates is the intercalation of R275 to plug the hole left by the extruded nucleobase (59, 60). Due to the decreased dynamics of DNA in the dyad region (47, 54), there may be a subset of TDG-NCP complexes for which intercalation of R275 is slowed, and thus requires a conformational change in the NCP in order to proceed.…”
Section: Discussionmentioning
confidence: 99%
“…[]. The MSM approach was used to model DNA base pair mismatch repair process and to study the dynamics of the thymine DNA glycosylase . Even though the MSM is able to simulate long‐time dynamics, obtaining reliable transition matrix elements requires extensive configurational sampling through MD simulations.…”
Section: Methodsmentioning
confidence: 99%
“…The glycosylase proteins uracil DNA glycosylase, thymine DNA glycosylase, and MutM have been studied through atomistic MD simulations. In particular, the base flipping process in thymine DNA glycosylase was studied by first driving the DNA–protein complex from an intrahelical to extrahelical state, which was followed by 300 100‐ns simulations all initialized along the base‐flipping pathway for a total of 30 µs, Figure . The results of these simulations were used to construct MSMs describing the kinetics of transition between 500 and 800 microstates that characterize the base‐flipping process.…”
Section: Computer Simulations Of Dna Replication and Repair Machinerymentioning
confidence: 99%
See 1 more Smart Citation